46.5k views
4 votes
If x^(y)=5^(x-y) then dy/dx=​

If x^(y)=5^(x-y) then dy/dx=​-example-1
User Henry Dang
by
4.7k points

1 Answer

7 votes

First, rewrite


x^y=e^(\ln x^y)=e^(y\ln x)


5^(x-y)=e^{\ln5^(x-y)} = e^(\ln(5)(x-y))

Now, differentiate both sides using the chain rule:


(\mathrm d\left(e^(y\ln x)\right))/(\mathrm dx)=(\mathrm d\left(e^(\ln(5)(x-y))\right))/(\mathrm dx)


e^(y\ln x)(\mathrm d(y\ln x))/(\mathrm dx)=e^(\ln(5)(x-y))(\mathrm d(\ln(5)(x-y)))/(\mathrm dx)


x^y\left((\mathrm dy)/(\mathrm dx)\ln x+y(\mathrm d(\ln x))/(\mathrm dx)\right)=\ln(5)5^(x-y)\left((\mathrm d(x))/(\mathrm dx)-(\mathrm dy)/(\mathrm dx)\right)


x^y\left(\ln x(\mathrm dy)/(\mathrm dx)+\frac yx\right)=\ln(5)5^(x-y)\left(1-(\mathrm dy)/(\mathrm dx)\right)


\left(x^y\ln x+\ln(5)5^(x-y)\right)(\mathrm dy)/(\mathrm dx)=\ln(5)5^(x-y)-yx^(y-1)


(\mathrm dy)/(\mathrm dx)=(\ln(5)5^(x-y)-yx^(y-1))/(x^y\ln x+\ln(5)5^(x-y))

User Nauman Tariq
by
6.0k points